Academic Pathfinders - Gumport, Patricia J (Greenwood Publishing Group, Incorporated, 2002)
Intro – Contents – Series Foreword – Preface – Introduction – 1 The Dynamic Nature of Academic Knowledge – 2 Academic Feminism: Antecedents, Initiatives, and Unresolved Issues – 3 Investigating Knowledge Creation – 4 The Pathfinders' Breakthroughs – 5 Knowledge Creation in the Disciplines: History, Sociology, and Philosophy – 6 Alternative Academic Pursuits: The Pathtakers and Forerunners – 7 Changing Conditions for Knowledge Creation – Appendix: Notes on the Research Design and Methods – Bibliography – Index.
Description based on publisher supplied metadata and other sources
Keywords: Women in higher education; Feminism and education; Learning and scholarship; Women college students; Women college teachers; Electronic books